2016
DOI: 10.1080/21505594.2016.1212154
|View full text |Cite
|
Sign up to set email alerts
|

Heart aging measured with coronary artery calcium scoring and cardiovascular risk assessment algorithms in HIV infected patients

Abstract: ABTRACT Many sources have highlighted the high incidence of premature cardiovascular events in HIV infected patients. This raises the suspicion of an accelerated aging of the vascular system in this disease characterized by chronic systemic subliminal inflammation and immune dysregulation. Unfortunately all currently available risk assessment algorithms based on traditional risk factors, and even those containing more HIV-specific factors, fail to accurately predict risk in a large proportion of patients. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A higher incidence of atherosclerosis among HIV-infected patients has been demonstrated in previous studies [ 14 - 16 ], and subclinical atherosclerosis can be assessed using the CAC score [ 17 - 19 ]. In the present study, we evaluated the usefulness of MDCT in quantifying the progression of coronary calcium levels and assessing the evolution of cardiovascular risk in a cohort of patients with long-term HIV.…”
Section: Discussionmentioning
confidence: 98%
“…A higher incidence of atherosclerosis among HIV-infected patients has been demonstrated in previous studies [ 14 - 16 ], and subclinical atherosclerosis can be assessed using the CAC score [ 17 - 19 ]. In the present study, we evaluated the usefulness of MDCT in quantifying the progression of coronary calcium levels and assessing the evolution of cardiovascular risk in a cohort of patients with long-term HIV.…”
Section: Discussionmentioning
confidence: 98%
“… 57 Our findings are consistent with prior literature, including an earlier, more limited review published in 2015, which found that participants with HIV have a higher prevalence of noncalcified plaques, which may be more prone to erosion and rupture. 4 , 5 , 6 , 10 , 29 , 32 , 33 In prior studies assessing actual cardiovascular events in patients with HIV compared with patients without HIV, there seems to be a consensus that patients with HIV are at increased risk of coronary events, in the range of 1.25‐ to 1.75‐fold higher risk. 65 , 66 , 67 , 68 , 69 , 70 The higher prevalence of noncalcified plaque and possibly earlier onset of CAC (as suggested by prior studies and this meta‐analysis), may explain the higher risk of CVD observed in patients with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…3 , 4 Because traditional risk factor calculators may not adequately capture the full extent of the CVD risk in this population, CT imaging markers such as coronary artery calcium (CAC) may be useful to fill in this gap for risk assessment. 5 Prior studies have suggested that patients with HIV have a higher burden of subclinical atherosclerosis, including carotid stenosis and accelerated coronary aging based on CAC score measures. 6 , 7 , 8 Additionally, asymptomatic patients with HIV have been reported to have higher rates of noncalcified plaques in some studies, 6 which are considered higher risk for rupture leading to cardiac events.…”
mentioning
confidence: 99%
“…Vascular age assessment goes beyond any statistical probability of risk and allows to identify patient vulnerability in patients with preclinical cardiovascular disease. 22 Finally, it may be inappropriate to utilize in HIV patients cardiovascular risk prediction algorithms (namely Framingham Risk score and ASCVD) calibrated to predict an "atherosclerotic event" in the general population, to estimate the risk of events which, in more than 50% of the cases, are non-atherosclerotic in HIVC patients, including sepsis, vasospasm due to cocaine use, anemia, acute volume fluctuations etc. 23 Future studies may need to address the calibration of various algorithms to separate the risk of type-1 from type-2 MI.…”
mentioning
confidence: 99%